Standardy delegalizacji partii politycznych w świetle orzecznictwa Europejskiego Trybunału Praw Człowieka — zagadnienia wybrane - Ossowska-Salamonowicz, Dobrochna; Giżyńska, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article presents selected issues related to delegalization of political parties. The political parties are indispensable institutions in the systemic life of a democratic state. The authors analyze selected judgments of the European Court of Human Rights related to the standards of delegalization of political parties. The authors conclude that in the existing case law of the ECHR, the main focus is on the external activities of political parties. In determining whether a political party is undemocratic, the focus is primarily on the aims and practices of the party.
Keywords: partie polityczne; delegalizacja; rozwiązanie partii politycznych; ETPCz; demokracja walcząca